Homozygosity of the TT methylenetetrahydrofolate reductase C677T genotype is an independent long-term predictor of cardiac death in patients with premature myocardial infarction. (3rd July 2021) - Rallidis, Loukianos S.; Kosmas, Nikolaos; Stathopoulou, Eleni; Rallidi, Maria; Gialeraki, Argyri
Abstract: Background: Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism is the main genetic modulator of homocysteine. Data suggest a potential association of homozygosity for the TT MTHFR genotype with premature myocardial infarction (MI). We explored whether TT homozygosity is associated with long-term prognosis in patients with premature ST-segment elevation MI (STEMI). Methods: A total of 265 consecutive patients who had survived their first STEMI ≤35 years of age were followed for a median of 8 years (5–12). Primary endpoints were cardiac death and secondary endpoints were hospitalizations for acute coronary syndrome, myocardial revascularization, arrhythmic event or ischemic stroke. Serum lipids, homocysteine, folate levels were measured at baseline and all patients were also tested for the MTHFR C677T polymorphism. Results: During follow-up 14 patients died (cardiac death) [5.3%] while 84 (31.7%) met the secondary endpoints. In univariate Cox regression analysis TT homozygosity predicted the occurrence of cardiac death (Hazard ratio (HR): 4.071; 95% confidence interval (CI): 1.404–11.809, p  = .010) but not the occurrence of secondary endpoints (HR: 0.877; 95% CI: 0.479–1.605, p  = .669). TT homozygosity remained an independent predictor of cardiac death after adjustment for conventional risk factors (i.e., sex, diabetes mellitus, hypertension, family history of premature coronary artery disease [CAD]) [HR: 4.350; 95% CI: 1.472–12.856, p  = .008]. The association also remained after adjustment for left ventricular ejection fraction or the presence of significant CAD. Conclusions: Homozygosity for the TT MTHFR is an independent long-term predictor of cardiac death in patients with premature STEMI.